Management and Early Outcomes of Bile Duct Injuries at University Teaching Hospital - Bhandari, Suyog; Thapa, Pradip; Sharma, Deepak; Maharjan, Narendra; Pradhan, Sumita; Kandel, Bishnu Prasad; Joshi Lakhey, Paleswan; Bhandari, Ramesh Singh (Journal of Institute of Medicine Nepal, 2024)
Introduction Bile duct injury (BDI) management depends upon the type, clinical presentation, available resources and expertise. Some BDI may be managed with endoscopic intervention with Endoscopic Retrograde Cholangio-pancreaticography (ERCP), sphincterotomy and/or stenting while others may require complex surgery and percutaneous interventions by interventional radiologists (IR). This study aimed to evaluate the management strategies and early outcomes of bile duct injuries at Tribhuvan University Teaching Hospital. Methods In this retrospective analysis, bile duct injuries in patients treated at Tribhuvan University Teaching Hospital, Kathmandu, Nepal over a period of two years were included (January 2020 to December 2022). In this study we have described the clinical presentation, Strasberg classification of BDI grade, different management techniques and their early outcomes. We calculated number and percentages for categorical variables, mean and standard deviation for continuous data. Results Out of 26 bile duct injuries, 12 (46.2%) patients underwent surgical management, 9 (34.6%) underwent percutaneous intervention and 5 (19.2%) underwent endoscopic intervention. Majority of the patient 15 (57.7%) had stricture as an indication for management. Patients who underwent surgical, endoscopic, and percutaneous management showed good early outcomes in 12, 5, and 8 patients respectively. The mean duration of hospital stay was 11.8±5.2 days and CCI was 15.2±9.7, for patients with index presentation who underwent surgery. Conclusion Management of bile duct injuries require multidisciplinary team approach and favorable outcomes can be achieved when managed with expertise at tertiary centers. Surgical management remains essential for complex cases, while percutaneous and endoscopic interventions offer viable alternatives for less severe injuries.